PENGARUH PROFITABILITAS, LEVERAGE, KEPEMILIKAN INSTITUSIONAL, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA - Gunawan, Agnes Elvina; Bangun, Nurainun (Jurnal Paradigma Akuntansi, 2025)
This research was conducted to gain empirical evidence about the effect of profitability, leverage, institutional ownership, and firm size on the earnings management of primary consumer sector companies food and beverage sub sector listed on the IDX in 2017-2021. In this study, the purposive sampling method was used to obtain a valid sample of 139 data from 33 companies after outlier was conducted. This study uses multiple linear regression method to test the hypothesis and the data is processed using SPSS version 26 and Microsoft Excel 2021. The findings show that profitability has no positive effect on earnings management, leverage has negative effect on earnings management. While institutional ownership and firm size have no negative effect on earnings management.